A influência da Universidade Federal de São Carlos na evolução da expansão urbana do município de São Carlos - SP - Tiburcio, Isabella Pizarro [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The county of São Carlos was boosted by the growth of the coffee cycle in the region - a historical process of fundamental importance for the development of brazilian economy - responsible for the beggining of urban expansion and industrialization process. On the 1970s, the Federal University of São Carlos (UFSCar) has been installed, generating the expansion of local research centers and the technological base, which has expanded the municipal vocation for the high technology industry. Still in the same decade, there has been an intensification in the growth of the population of São Carlos, both by the increase of industrialization and by the implementation of research and teaching centers. Considering the absence of scientific papers that relate more deeply the urban expansion that occurred in the county of São Carlos in recent decades stimulated by its largest university (UFSCar), the main objective of this research was to analyze the influence of the federal institution in the intense growth of the urban area of São Carlos. For that, a survey and analysis of the bibliography dealing with the territorial formation of the municipality and the process of urban expansion in São Carlos were carried out, as well as those that present the study of the implementation of the universities in the city. The cartographic base of São Carlos (1: 10,000) was organized, selecting the most important data for the research. This served as a subsidy for the elaboration of the thematic map of urban expansion, which aimed to update the map of Santoro (2012). A survey was also carried out to identify the housing neighborhood of the academics, in order to elaborate the maps of the distribution of the academic population by the municipality. Thus, it was possible to analyze the process of urban expansion of São Carlos and how much the university was able to contribute and still contributes to the growth of its urban network. Because of the importance of...

O município de São Carlos teve seu crescimento alavancado pela intensificação do ciclo do café na região - processo histórico de fundamental importância para o desenvolvimento da economia brasileira - responsável pelo princípio da expansão urbana e pelo início do processo de industrialização. A partir dos anos 1970, houve a instalação da Universidade Federal de São Carlos (UFSCar), gerando a ampliação dos centros de pesquisas locais e da base tecnológica, o que expandiu a vocação municipal para a indústria de alta tecnologia. Ainda na mesma década, houve a intensificação no crescimento da população são-carlense, tanto pelo aumento da industrialização como pela implementação dos centros de pesquisa e ensino. Considerando-se a ausência de trabalhos científicos que relacionem de forma mais profunda a expansão urbana ocorrida no município de São Carlos nas últimas décadas estimulada pela sua maior universidade (UFSCar), o principal objetivo dessa pesquisa foi analisar a influência da instituição federal no intenso crescimento da área urbana de São Carlos. Para tanto, realizou-se o levantamento e a análise da bibliografia que trata da formação territorial do município e do processo de expansão urbana são-carlense, bem como aquelas que apresentam o estudo da implementação das universidades no município. A base cartográfica de São Carlos (1:10.000) foi organizada, selecionando-se os dados mais importantes para a pesquisa. Essa serviu de subsídio para a elaboração do mapa temático da expansão urbana, permitindo-se atualizar o mapa de Santoro (2012). Ainda, foi efetuado um levantamento de informações para a identificação do bairro de moradia dos acadêmicos, a fim de elaborar os mapas da distribuição da população acadêmica pelo município. Assim, foi possível analisar o processo de expansão urbana de São Calos e o quanto a universidade contribuiu e, ainda hoje, contribui para o...
Keywords: Universidade Federal de São Carlos; Crescimento urbano; Geografia urbana; Cartografia; Planejamento urbano; São Carlos (SP)